Utilizing social science data from river recreationists to inform river management. (1st February 2022) - Doeblin, Dylan; Brunson, Michael; Sharp, Ryan L.; Brownlee, Matthew T.J.
Abstract: River recreation often contributes to ecological degradation – a primary concern for river management professionals. Using social science data to inform ecological management helps mitigate recreational impacts, particularly at sites that experience high recreation use. This paper demonstrates the utility of an approach to collect, display, and use social data based on an indicators and thresholds approach at Buffalo National River in Arkansas (BUFF). Specifically, we presented a series of digitally manipulated photographs to river recreationists at BUFF that depicted varying levels of use, or density of use, to identify social thresholds – the levels of use deemed unacceptable by river users. We coupled the photos with quantitative questionnaires and found that paddlers, anglers, and campers thought that moderate to high‐density levels were unacceptable. Pairing such data with empirical evidence of ecological degradation born from recreation use (e.g., erosion, water quality issues) provides a robust and defensible justification for a range of management actions, including altering use levels and river access. The research methods presented in this paper are transferable to a range of high‐use rivers and waterways, and thus provide a blueprint for river professionals who by design or default interface with recreation and ecological resources. In the end, combining social and ecological data can fortify management decisions and decrease associated conflicts among important groups of river recreationists.